The complete chloroplast genome of Pholidota imbricata (Orchidaceae) - Rao, Wen-Hui (Mitochondrial DNA B Resour, 2019)
Pholidota imbricata belongs to tribe Coelogninae in Orchidaceae distributed in Sichuan, Xizang, and Yunnan. Here, we report the first complete chloroplast (cp) genome and the cp genome features of P. imbricata. The complete cp genome sequence of P. imbricata is 159,292 bp in length and presented a typical quadripartite structure including one large single-copy region (LSC, 87,515 bp), one small single-copy region (SSC, 20,999 bp), and two inverted repeat regions (IRs, 25,389 bp each). The cp genome encoded 141 genes, of which 108 were unique genes (80 protein-coding genes, 24 tRNAs, and 4 rRNAs). The phylogenetic relationships show that P. imbricata is sister to the species of the genus Pleione in tribe Coelogninae.